When pride still mattered a life of Vince Lombardi - Maraniss, David (New York Simon & Schuster, 1999)
More than any other sports figure, Vince Lombardi transformed football into a metaphor of the American experience. The son of an Italian immigrant butcher, Lombardi toiled for twenty frustrating years as a high school coach and then as an assistant at Fordham, West Point, and the New York Giants before his big break came at age forty-six with the chance to coach a struggling team in snowbound Wisconsin. His leadership of the Green Bay Packers to five world championships in nine seasons is the most storied period in NFL history. Lombardi became a living legend, a symbol to many of leadership, discipline, perseverance, and teamwork, and to others of an obsession with winning. In When Pride Still Mattered, Pulitzer Prize-winning author David Maraniss captures the myth and the man, football, God, and country in a thrilling biography destined to become an American classic.
Includes bibliographical references (p. [517]-518 )
Keywords: Lombardi, Vince. Green Bay Packers (Football team) -History. Football coaches-United States -Biography.